Retinoblastoma , our experience - Coutinho, I (2013)
Introduction: The retinoblastoma is the most common malignant ocular tumor of childhood with an incidence of 1: 15000 – 20000 births and it is due to a mutation on RB1 gene, a tumoral supressor gene. The average age of diagnosis is 12 months in bilateral and 24 months in unilateral cases. Late diagnosis usually means lost of eye function or even death, that’s why the early screening in every child is so critical. Goals: Review and approach the diagnosis and current treatment of retinoblastoma. Describe the experience in treatment and follow-up of the children in our hospital, a Portuguese not central hospital near Lisbon. Methods: Review of the literature. Retrospective evaluation of the patients treated in the last 8 years in our hospital, together with the Oncology Portuguese Institute of Lisbon, using local (lasertherapy, cryotherapy and enucleation) and systemic (chemotherapy) therapy. Results: 7 patients were treated with unilateral retinoblastoma and 4 with bilateral disease. They were send to us by the assistant physician (pediatrician, ophthalmologist and general practice physician) because a positive familiar history, emerge of leucocory or strabismus. The average age was 21 months and the most frequent group was D according international classification system for intraocular retinoblastoma In the 8 eyes where conservative treatment was possible, after chemoreduction they were submitted to LASER Árgon or cryotherapy, according to the tumor location. In Five of these eyes there were also treated with transpupilar thermotherapy (TTP), brachytherapy, intra-vitreous or intra -arterial chemotherapy, in Laussane, at the Jules-Gonin Ophthalmic Hospital. 4 eyes were first enucleated and another 3 were secondary enucleated. The authors exhibit images taken before, during and after treatment Conclusion: Leucocory and strabism are the main forms of presentation of retinoblastoma. The treatment depends of the size of the tumor, laterality, eyesight potential and age of the child. The main therapeutic approaches are systemic chemotherapy with local therapies like cryotherapy, lasertherapy ,TTP, intra-arterial and intra-vitreous chemotherapy, brachytherapy and enucleation. Earlier diagnosis and treatment increase the number of patients that remain free of disease and preserve the vision. The treatment of these patients require a multidisciplinar team and frequent re-evaluations to detect recurrence, diagnosis of other tumors, such as sarcomas, that have increased incidence in survivors, as the genetic counseling to the patient and parents.